From Mandailing Land to Haramayn: Mandailing Ulama and the Religious Sciences in the Early 20th Century - Ja'far Ja'far (Sekolah Tinggi Agama Islam Sumatera Medan, 2022)
Mecca and Medina, also known as Haramayn, are the two holy cities of Muslims and serve as the intellectual and spiritual centers of the Islamic world. At the beginning of the 20th century, religious students from the archipelago visited these cities to perform the pilgrimage and continued their studies. While researchers have uncovered the role and network of Indonesian ulama, not all ulama groups have been successfully uncovered. This article examines the role of the Mandailing ulama, particularly those with the surname Nasution, in preserving religious sciences in the Tapanuli Residency in the early 20th century. The ulama discussed in this study include Sheikh ‘Abd al-Qadir al-Mandily (Nasution), Sheikh Muhammad Ja’far Nasution, and Sheikh Musthafa Husein Nasution. This is a literature study with a historical approach. Kuntowijoyo’s historical research model serves as a reference in writing this article, and al-Ghazâlî’s opinion about the classification of knowledge is the main theory used to analyze research topics. This article argues that the Mandailing ulama, particularly those with the surname Nasution, actively preserved religious sciences in the Tapanuli Residency after studying at Masjidilharam in Mecca, Saudi Arabia. They later became the primary agents of teaching religious sciences according to the Sunni Islamic tradition in their respective areas. The results of this study have implications for the strengthening of literature and theory on the role and network of Indonesian ulama.